Thinking the Pandemic from the Philosophy of Health: a Proposal for Discussion - Ochoa Pineda, Amada Cesibel; Aranda Torres, Cayetano José (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
This essay, which is part of a health philosophy project, deals with the impossibility of understanding SARC-Cov2, and the rest of nature, if we are not able to understand the human sense of knowledge and science, and the socio-cultural conditions of technological civilization and globalized life, without which the pandemic would not have been possible or, at least, its effects would have been mitigated and located in space / time. It concludes with the need to make an ethical approach in relation to freedom and responsibility in the era of globalization.